Diversity of conidial fungi and some abiotic variables of the water after the reopening of the Pirarungaua stream in the Jardim Botânico, São Paulo, São Paulo State, Brazil - Schoenlein-Crusius,Iracema H. (2016)
ABSTRACT To evaluate the fungal diversity in the Pirarungaua stream reopened after remaining channeled about 40 years in the Botanical Garden of São Paulo, Brazil, two experiments in the cold and dry season and two in the hot and rainy season were performed. Leaves of Tibouchina pulchra Cogn and mixed leaf litter were confined in nylon litter bags, submerged and collected monthly, together with free leaf litter samples. Some abiotic factors were measured in the water. The leaves were fragmented, incubated in sterile water at 22 ºC and microscopically analyzed. We identified 33 conidial fungal taxa, among which, 23 are new to this area. Comparing seasons, the similarity of the mycota of confined T. pulchra leaves corresponded to 39% and to 56% regarding the confined mixed leaf litter. Similarities of 48-50% occurred between the mycota of confined and free leaf litter samples. Confined leaves showed a tendency to support higher numbers of species, whereas some rare fungi like Ulocoryphus mastigophorus Michaelides L. Hunter & W.B Kendr were more frequent in free leaf litter. Based on the results, it is recommended to monitor the limnological conditions of the stream and to promote awareness among the local population and visitors about the importance of a water body, even artificial, for the establishment of microclimatic features, and for the biodiversity of fungi.